1981
DOI: 10.1007/bf00342089
|View full text |Cite
|
Sign up to set email alerts
|

Subacute reactions to intrathecal Amipaque (metrizamide), conray and dimer X: A structural and ultrastructural study

Abstract: Adult New Zealand rabbits were injected intrathecally with 200 or 300 mgI/ml of metrizamide, meglumine iocarmate or meglumine iothalamate. They were placed in the Trendelenburg position for 20 min and allowed to survive for 1, 2 or 3 weeks. Sacrifice was by intraarterial perfusion of aldehydes under anesthesia followed by preparation of brain and major venous sinuses for light and electron microscopy. Major findings were subpial edema and inflammatory reaction of superficial brain, leptomeninges, subarachnoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…As various neurotoxic effects can be seen in both rodents and humans, neurotoxic studies in rodents may have predictive value for neurotoxic effects in humans [ 55 ]. In their study of adult rabbits having had intrathecal injection of both ionic and nonionic contrast media, Lee et al found subpial edema as well as acute and chronic inflammation; these conditions were most severe after ionic injection and milder after nonionic injection [ 56 ]. Miyazawa et al infused rat blood with an ionic CM, which deformed red blood cells and in turn induced cerebral edema, destruction of the BBB, and animal death.…”
Section: Discussionmentioning
confidence: 99%
“…As various neurotoxic effects can be seen in both rodents and humans, neurotoxic studies in rodents may have predictive value for neurotoxic effects in humans [ 55 ]. In their study of adult rabbits having had intrathecal injection of both ionic and nonionic contrast media, Lee et al found subpial edema as well as acute and chronic inflammation; these conditions were most severe after ionic injection and milder after nonionic injection [ 56 ]. Miyazawa et al infused rat blood with an ionic CM, which deformed red blood cells and in turn induced cerebral edema, destruction of the BBB, and animal death.…”
Section: Discussionmentioning
confidence: 99%